Urban Development in Longyearbyen: Dealing with Local Challenges in a Town that Serves as a Tool for Svalbard Policies ... - Meyer, Alexandra (Zenodo, 2022)
Abstract Svalbard’s main urban centre, Longyearbyen, is a town in constant transition. Established as a coal mining camp, it developed into a mono-industrial company town, was then transformed into a “normal” Norwegian family town, and is today profoundly impacted by climate change and undergoing economic, social and cultural changes at high speed. In this chapter, I examine urban planning and development in Longyearbyen, looking at historical developments and discussing current challenges. I trace the development of the town and show how the societal transformations beginning in the 1970s led to an institutionalization and formalization of urban planning. I then discuss three main issues and challenges related to community development today, brought about by rapid climate and socio-economic change: securing the town against environmental changes, the housing crisis, and a changing identity. I argue that throughout its history, Longyearbyen’s function for the Norwegian state as an upholder of presence and ...